2016
DOI: 10.1590/s1984-29612016075
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Neospora caninum and Toxoplasma gondii antibodies in dogs from rural properties surrounding a biological reserve, Espirito Santo, Brasil

Abstract: The aim of this study was to determine the presence of antibodies to Neospora caninum and Toxoplasma gondii in serum samples of 187 dogs from 30 rural properties surrounding Córrego do Veado Biological Reserve, Espírito Santo State, Brazil. The Reserve is one of the last lowland Atlantic Forest remnants of the region, surrounded by agriculture farms and cattle pastures. The presence of IgG antibodies was determined by the Indirect Fluorescent Antibody Test for T. gondii (cut-off 1:16) and N. caninum (cut-off 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 17 publications
2
9
0
3
Order By: Relevance
“…This percentage is considered high compared to that found in higher tham the present study. Acosta et al (2016) analyzed samples of 187 dogs from 30 properties in the state of Espirito Santo and found an occurrence of 11.76%, which is similar to the results of this study in the west of Paraná. Nogueira et al (2013) evaluated the prevalence of protozoa in dogs from urban and rural areas in the State of Minas Gerais and found that 11.4% of the samples had positive results: 13.78% in dogs from rural areas and 8.24% in dogs from urban areas.…”
Section: Seroprevalence and Risk Factorssupporting
confidence: 87%
See 2 more Smart Citations
“…This percentage is considered high compared to that found in higher tham the present study. Acosta et al (2016) analyzed samples of 187 dogs from 30 properties in the state of Espirito Santo and found an occurrence of 11.76%, which is similar to the results of this study in the west of Paraná. Nogueira et al (2013) evaluated the prevalence of protozoa in dogs from urban and rural areas in the State of Minas Gerais and found that 11.4% of the samples had positive results: 13.78% in dogs from rural areas and 8.24% in dogs from urban areas.…”
Section: Seroprevalence and Risk Factorssupporting
confidence: 87%
“…Only two animals showed titers of 400 (10.52%) and one animal had a titer of 800 (5.26%). However, Nogueira et al (2013) found anti-N. caninum antibodies in dogs ranging from 50 to 6400, with a Acosta et al (2016) found a greater number of dogs with titers between 800 and 1600. The presence of N. caninum seropositive dogs was not considered a risk factor for seropositivity in cattle, as it was not statistically significant ( Figure 1).…”
Section: Seroprevalence and Risk Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 9.18% prevalence of seropositive dogs found is similar to studies conducted in other Brazilian states on dogs from rural areas. Studies in the regions of Minas Gerais (NOGUEIRA et al, 2013), Espírito Santo (ACOSTA et al, 2016), andParaná (SNAK et al, 2018) showed N. caninum seropositivity in 13,78%, 11.76%, and 11.66% of the animals analyzed, respectively. On the other hand, few studies showed higher percentages, for example, Teixeira (2008) detected seropositivity in 62.37% of dogs in the milk producing properties of Maranhão, and Benetti et al (2009) reported positivity in 66.7% of the dogs inhabiting dairy farms in Mato Grosso.…”
Section: Discussionmentioning
confidence: 99%
“…Information about the epidemiology of neosporosis and toxoplasmosis has been reported in several places in Brazil, proving the widespread circulation of these protozoans (Acosta et al, 2016;Brasil et al, 2018;Cerqueira-Cézar et al, 2017;Langoni et al, 2014). The presence of anti-N. caninum antibodies has also been reported in different animals, including cattle and dogs, in the state of Mato Grosso (Benetti et al, 2008;Benetti et al, 2009;Boa Sorte et al, 2015;Melo et al, 2012;Rodrigues et al, 2016).…”
Section: Introductionmentioning
confidence: 99%